Algunas reflexiones sobre la didáctica de la geometría - Gamboa Araya, Ronny (2009)
This paper pretends to describe the problem related to the teachingand learning of geometry in the classroom from a constructive perspective, which foments the sensitization of the teacher; moreover impact positively in his/her pedagogic practice.A reflexive analysis has been developed considering different elements so that, the reader can have arguments that justify the relevance of studying this area.